Rapamycin inhibits tamoxifen-induced endometrial proliferation in vitro as a pilot approach for endometrial protection in breast cancer - Akiko Nakamura; Yuji Tanaka; Tsukuru Amano; Akie Takebayashi; Akimasa Takahashi; Tetsuro Hanada; Yutaka Yoneoka; Shunichiro Tsuji; Takashi Murakami (Scientific Reports)
Abstract Tamoxifen, a common adjuvant therapy for hormone receptor-positive breast cancer, is associated with an increased risk of endometrial pathologies, such as hyperplasia, polyps, and carcinoma. This study investigates rapamycin, an mTOR inhibitor, as a potential novel strategy for preventing tamoxifen-induced endometrial proliferation. This in vitro study utilised endometrial stromal cells isolated from infertile women. The cells were treated with tamoxifen alone or in combination with rapamycin, and proliferation was assessed using the CCK-8 assay. The activation of the mTOR pathway, as well as apoptosis and cell cycle markers, was evaluated by Western blotting to elucidate the molecular mechanisms underlying these effects. The study design emphasised simulating clinically relevant exposure levels. Tamoxifen significantly increased endometrial cell proliferation in a dose-dependent manner. Rapamycin effectively inhibited this proliferation, even at concentrations lower than those typically observed in clinical settings. Quantitative analysis by Western blotting showed activation of the mTOR pathway and cell cycle in the tamoxifen group, and inhibition of these pathways in the tamoxifen plus rapamycin combination group, whereas there was no change in apoptosis. In conclusion, rapamycin shows promise as a prophylactic agent against tamoxifen-induced endometrial pathologies, with potential implications for fertility preservation and endometrial protection in breast cancer patients.